TELAAHAN PENERAPAN SISTEM INFORMASI AKUNTANSI DENGAN MYOB UNTUK PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PSAK NO. 1 PADA CV. GRAPH PRINTING - Adri Wihananto (Jurnal Ilmiah Binaniaga, 2010)
Financial statements represent end result from applying an information accounting system. Therefore, to yield good financial statement needed a good information system also. With existence of computerized accounting information system it is provided that accounting information system will walk better and the yielded to financial statements become more accurate and complete. The objective of this research is to know accounting system which previously exists at CV Graph Printing. Others, this research also aim to apply computerized accounting information system with MYOB. This application is expected could help company make good financial statement. CV Graph Printing represent a company moving in the field of printing office. The effort area experienced by this company for example setting (invitation, brochure, visiting card, etc.), screening (clothes, invitation, plastic, etc.), and print (book, invitation, note, etc.). The result of research indicate that accounting information system which preexist at company, that is manual administrate system is not be adequate again. Accounting record process for transactions that happened in company have never been done. Others also the transaction evidences are not kept better. The most important fact is that during the time the company not at all own financial statement so that the owner do not know their company performance during the time. With existence of applying MYOB in its accounting information system, transaction record become easier and quickly. Financial statement could visible any time we wish. Others also, financial statement yielded become more accurate and complete as according to Financial Accounting Standard (FAS) which is validKeywords: accounting information system, MYOB, financial statement